High Blood Pressure Increases the Risk of Poor Outcome at Discharge and 12‐month Follow‐up in Patients with Symptomatic Intracranial Large Artery Stenosis and Occlusions: Subgroup analysis of the CICAS Study. (28th April 2015) - Yu, Dan‐Dan; Pu, Yue‐Hua; Pan, Yue‐Song; Zou, Xin‐Ying; Soo, Yannie; Leung, Thomas; Liu, Li‐Ping; Wang, David Z.; Wong, Ka‐Sing; Wang, Yi‐Long; Wang, Yong‐Jun; the Chinese Intracranial Atherosclerosis (CICAS) Study Group
Summary Aims The purpose of this study was to discuss the relationship between blood pressure and prognosis of patients with symptomatic intracranial arterial stenosis. Methods Data on 2426 patients with symptomatic intracranial large artery stenosis and occlusion who participated in the Chinese Intracranial Atherosclerosis (CICAS) study were analyzed. According to the JNC 7 criteria, blood pressure of all patients was classified into one of the four subgroups: normal, prehypertension, hypertension stage I, and hypertension stage II. Poor outcomes were defined as death and functional dependency (mRS 3‐5) at discharge or at 1 year. Results For patients with intracranial stenosis of 70% to 99%, the rate of poor outcome at discharge was 19.3%, 23.5%, 26.8%, and 39.8% (P = 0.001) for each blood pressure subgroup. For patients with intracranial large artery occlusion, the rates were 17.6%, 22.1%, 29.5%, and 49.8%, respectively (P < 0.0001). The rate of poor outcome at 12‐month follow‐up was 12.6%, 15.3%, 28.5%, and 27.9% (P = 0.0038) in patients with stenosis of 70% to 99% for each blood pressure subgroup and 11.6%, 21.5%, 23.9%, 35.1% (P < 0.0001) in patients with occlusion. Conclusions For patients with severe intracranial arterial stenosis or occlusion, higher hypertension stages are associated with an increased risk of poor outcome at discharge and 12‐month follow‐up.